Meningkatkan Kemampuan Pemecahan Masalah Matematis pada Materi KPK Menggunakan Alat Peraga Dakon Matematika di Kelas V SDN Sukanagalih - Fadilah, Dinan Raihan; Zahrah, Riza Fatimah; Sidik, Geri Syahril (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve students' mathematical problem-solving skills through the use of the Dakon Math teaching aid. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were 30 fifth-grade students. Data collection techniques included observation, tests, and documentation. The research instruments consisted of observation sheets for teacher and student activities, as well as test questions in the form of story problems that measure problem-solving abilities. The results indicate a significant improvement in students' mathematical problem-solving skills from the pre-action phase to cycles I and II. The average score of students in the pre-action phase was 55.50, with a completeness rate of only 16.66%. After implementing the Dakon Math teaching aid, the average score in cycle I increased to 72.73 with a completeness rate of 56.67%, and in cycle II, it further rose to 79.27 with a completeness rate of 83.33%. These results demonstrate that the use of the Dakon Math teaching aid effectively aids students in understanding the fundamental concept of LCM and enhances their problem-solving abilities. Thus, it can be concluded that the Dakon Math teaching aid can serve as an effective alternative media for improving students’ mathematical problem-solving skills in the LCM topic at the elementary school level.